Meta-analysis of the effect of Internet plus nursing in patients with chronic wounds in China (“互联网+护理”在国内慢性伤口患者中应用效果的Meta分析) - HAN Mengfei (韩梦菲); LI Na (李娜); FENG Hongwei (封红伟) (中西医结合护理)
Objective To systematically review the application effect of Internet plus nursing in nursing of patients with chronic wounds in China. Methods Randomized controlled trials on the effect of “Internet + nursing” in nursing of chronic wounds were retrieved from CNKI, Wanfang Data, VIP, and CBM databases from the establishment to March 2024. RevMan 5. 3 software was used for meta-analysis. Results A total of 12 studies were included, involving 1092 patients with chronic wounds. Meta-analysis showed that compared with conventional care, “Internet + nursing” intervention could effectively improve the cure rate of treatment (MD=4. 43, 95%CI: 2. 88~6. 80, P＜0. 05), enhance patient self-care ability (MD=3. 69, 95%CL: 3. 38~4. 00, P＜0. 05), and improve patient satisfaction (MD=6. 96, 95%CL: 4. 15~11. 67, P＜0. 05). Conclusion Current evidences showed a positive effect of “Internet + nursing” on improving the nursing efficiency and quality of life of patients with chronic wounds. Therefore, the chronic wound nursing interventions based on “Internet + nursing” is an effective supplement to conventional nursing. (目的 系统评价“互联网＋护理”在国内慢性伤口患者中的应用效果。方法 检索中国知网(CNKI)、万方(Wanfang Data)、维普(VIP)、中国生物医学文献数据库(CBM)中关于“互联网+护理”干预对慢性伤口的文献, 检索时间为建库至2024年3月30日。采用RevMan 5. 3软件进行Meta分析。结果 纳入12项研究成果, 涉及慢性伤口患者1092例。Meta分析结果显示: 与常规护理相比, “互联网＋护理”干预能有效提高慢性伤口患者治愈率(MD=4. 43, 95%CI: 2. 88~6. 80, P＜0. 05), 提高自护能力(MD=3. 69, 95%CI: 3. 38~4. 00, P＜0. 05), 提高患者满意度(MD=6. 96, 95%CI: 4. 15~11. 67, P＜0. 05)。结论 当前证据表明, 与常规护理相比, “互联网+护理”能提高护理效率以及改善慢性伤口患者的生活质量, 是常规护理的有效补充。)